Connaissances à l’œuvre dans l’intervention complexe en ergonomie - Camille Jullienne; Fabien Coutarel; Marie-Pierre Poulossier; Gabin Gindro; Géraldine Rix-Lièvre (Revue d'anthropologie des connaissances)
This article examines the knowledge at work in a complex ergonomics intervention. To account for the sequence of events during the intervention, we mobilize an approach based on CMO configurations (context, mechanism, outcome –Nielsen, 2017). We are interested in the relationships that exist between the components of the intervention. This longitudinal extrinsic viewpoint is complemented by a second approach that focuses on the experience of the ergonomist. We seek to characterize the lived experience of specific moments of the intervention (Cahour et al., 2016). This internal perspective could enable us to characterize the concerns of the practitioner in relation to the experienced situation, and therefore to analyze the variation of these experiences, in connection with the evolution of CMO configurations. The questions we ask ourselves, then, are: how can we build and share knowledge about ergonomics intervention, so as to be able to assess the relevance of intervention modalities and understand what makes them valuable, optimize their models and discuss the underlying theories.